A near-infrared IIb fluorophore for in vivo imaging and image-guided therapy of ischemic stroke. (April 2023) - Qiao, Xue; Li, Yang; Wang, Wumei; Xiao, Yuling; Tian, Tian; Wang, Xiaobo; Luo, Haibin; Chen, Deliang; Meng, Xianli; Zeng, Xiaodong; Hong, Xuechuan
Abstract: Near-infrared II (NIR-II) functional dyes can diagnose various diseases in non-invasive conditions. Dynamic visualization of ischemic stroke has the potential to expedite stroke diagnosis and facilitates timely treatment to alleviate cerebral injury in the continuum of stroke care. However, there is still a lack of effective imaging methods to visualize the infarct area of ischemic stroke. In this study, we report a near-infrared II (NIR-II, 1–1.7 μm) fluorophore HLX with the unique twisted donor-acceptor π-architecture, which exhibits strong aggregation induced emission characteristics and high fluorescence quantum yield in the NIR-II window and near-infrared IIb (NIR-IIb, 1.5–1.7 μm) region. The whole-body vascular imaging with superior clarity using HLX dots was achieved. Most importantly, HLX dots was utilized to realize NIR-IIb fluorescence imaging of ischemic stroke in animals and dynamically monitor the therapeutic efficacy of salidroside for the first time. Our studies further demonstrate the neuroprotective effects of salidroside against cerebral ischemic injury through promoting angiogenesis. Superior biocompatibility enables HLX as a potential agent in the NIR-IIb region to light up the infarcted vessels and image-guided therapy of ischemic stroke. Graphical abstract: Image 1 Highlights: A near-infrared II functional dye HLX is synthesized with strong aggregation induced emission characteristics and high fluorescence quantum. The whole-body vascular imaging with superior clarity using HLX dots was achieved. HLX dots was utilized to dynamically monitor the ischemic stroke therapeutic efficacy of salidroside for the first time.